2020
DOI: 10.1101/2020.04.28.066365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of purifying and background selection on the inference of population history: problems and prospects

Abstract: ABSTRACTCurrent procedures for inferring population history are generally performed under the assumption of complete neutrality - that is, by neglecting both direct selection and the effects of selection on linked sites. We here examine how the presence of direct purifying and background selection may bias demographic inference by evaluating two commonly-used methods (MSMC and fastsimcoal2), specifically studying how the underlying shape of the distri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 118 publications
(205 reference statements)
2
42
2
Order By: Relevance
“…One simple but somewhat unsatisfactory solution is to approximate the effects of background selection across the genome by scaling effective population sizes with a factor drawn from empirical estimates of the effect of background selection across the genome [50]. A better solution would be to estimate the distribution of selection coefficients as part of the model [51]. This requires a generator that can simulate selection, for example SLiM [21], but would be much more computationally intensive than the coalescent simulations in the current approach.…”
Section: Discussionmentioning
confidence: 99%
“…One simple but somewhat unsatisfactory solution is to approximate the effects of background selection across the genome by scaling effective population sizes with a factor drawn from empirical estimates of the effect of background selection across the genome [50]. A better solution would be to estimate the distribution of selection coefficients as part of the model [51]. This requires a generator that can simulate selection, for example SLiM [21], but would be much more computationally intensive than the coalescent simulations in the current approach.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the difference between our results and those of Johri et al (2021) also leads to the fundamental question of the link between a PSMC curve and the IICR. As outlined in Mazet et al (2016) and several subsequent studies, the IICR is a theoretical function associated to a given evolutionary model (and sampling scheme), while the PSMC is an estimation of this theoretical quantity.…”
Section: Iicr Predictions and Psmc Estimationsmentioning
confidence: 59%
“…We found that PSMC estimations fit well our predictions for large chunks (10 6 and 10 5 ), but may highlight more complex and unpredicted patterns for smaller ones (Figure S7). This may explain the poor fit of our predictions with the PSMC results of Johri et al (2021), where the heterogeneity of N e was detectable only at very small scale (≤ 55kb).…”
Section: Iicr Predictions and Psmc Estimationsmentioning
confidence: 59%
“…Second, background selection, the loss of a linked neutral site from purifying selection on a deleterious allele, can potentially mimic patterns of selective sweeps and thus may impact the results of this study (Charlesworth et al 1993 (Johri, Riall, et al 2020;. The demographic strings calculated from PSMC used in this analysis also broadly agree in population size shape with other demographic estimates generated using other methods (e.g., Becquet and Przeworski (2007); Hey (2010)), therefore, background selection unlikely affects the demographic models used in analysis.…”
Section: Recent Attention Has Focused On Admixture Between Lineages Imentioning
confidence: 99%